Short selling and stock returns: evidence from the UK - Mohamad, Azhar; Jaafar , Aziz; Hodgkinson, Lynn; Wells, Jo (ELSEVIER, 2013)
The practice of shorting stocks was put forward as one of the causes of the recent financial crisis whereas Shiller (2003), for example, considers shorting an essential element of an efficient market. Shorting involves selling borrowed stocks and subsequently closing the position by purchasing and returning the stock to the lender. A profit will be realised if the stock’s price decreases. Shorting enables investors who do not own a perceived overvalued stock to sell. Using a high frequency UK dataset for the period between September 2003 and April 2010, our findings suggest shorting indicates evidence of overvalued stocks as significantly negative abnormal stock returns appear to follow an increase in shorting. These results do not hold, however, for shorting which occurs around the ex-dividend date. We further find that these results hold during the recent financial crisis.